2021
DOI: 10.3390/vaccines9101101
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Vectored Vaccines: A Legacy of the COVID-19 Global Crisis

Abstract: The COVID-19 pandemic represents a milestone in vaccine research and development in a global context. A worldwide effort, as never seen before, involved scientists from all over the world in favor of the fast, accurate and precise construction and testing of immunogens against the new coronavirus, SARS-CoV-2. Among all the vaccine strategies put into play for study and validation, those based on recombinant viral vectors gained special attention due to their effectiveness, ease of production and the amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…The data reported the ability of the vaccine to produce a heterologous protein capable of being recognized by the serum of animals naturally infected with FIV. These results corroborate that MVA is a vector capable of being engineered to produce heterologous proteins with the correct folding in mammal systems, which was extensively studied and reviewed elsewhere [ 33 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 83%
“…The data reported the ability of the vaccine to produce a heterologous protein capable of being recognized by the serum of animals naturally infected with FIV. These results corroborate that MVA is a vector capable of being engineered to produce heterologous proteins with the correct folding in mammal systems, which was extensively studied and reviewed elsewhere [ 33 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 83%
“…The better route of administration and frequency of booster dose administration is under investigation. The Oxford-AstraZeneca vaccine would be less effective against the beta variant, and the prospect of a “booster” dose for persons who have previously been vaccinated toward COVID-19 has been mentioned [ 190 ].…”
Section: Booster Dose Strategymentioning
confidence: 99%
“…This vaccine contains replication-defective Ad5 vectors expressing the full-length spike gene based on Wuhan-Hu-1. The phase I and II trials results suggest that this vaccine demonstrated a good safety profile [ 8 , 9 , 10 ]. Despite this information, the lack of authorization by the WHO for the Ad5-nCov vaccine generates uncertainty in the population; thus, it is important to gain more knowledge about the immunogenicity, efficacy, duration of protection, and side effects to contribute to an informed decision-making process for the health authorities.…”
Section: Introductionmentioning
confidence: 99%